방염처리 육송의 연소특성 연구 - 최정민(Choi, Jung-Min); 노호성(Ro, Ho-Seung); 진영화(Jin, Young-Hwa) (한국화재소방학회 논문지, 2011)
The combustion characteristic was evaluated for Pinus densiflora, used as a building material in Hanok, which were treated with two different flame retardant method. The specimen was brushed with flame retardant liquid two or three times and then let the specimen dehydrated during 24 h for spreaded treating. And the other specimen was soaked in the liquid for 72 h. The test methods were inflammability test using meker burner and heat release rate test using cone calorimeter. As a result for the tests, flame retardant treated specimens met the requirements of the inflammability and the spreaded treated method was more efficient than immersed method. The spreaded treated specimen had lower combustive properties than immersed specimen in TTI (time to ignition), PHRR (peak heat release rate), MLR (mass loss rate) and THR (total heat release). 본 논문에서는 한옥 부재로 사용되는 육송을 대상으로 도포법과 상압함침법의 방염처리 방법을 적용하여 각 연소특성을 평가하였다. 도포 처리는 시험체 표변에 2-3회 붓칠한 후 24h 건조하는 것을 3회 반복하였고, 상압함침 처리는 시험체를 약제 속에 72h 동안 함침시켜 처리하였다. 연소특성 평가방법으로는 멕켈버어너를 사용한 방염성능 시험, 콘칼로리미터를 사용한 열방출률 시험방법을 적용하였다. 시험 결과 방염성능에 있어서 두 가지 방법으로 처리한 시험체는 모두 현재 합판에 대한 성능기준을 만족하였으며, 상압함침 처리보다는 도포 처리한 시험체의 방염성능이 더 우수하게 나타났다. 열방출률 시험 결과로는 착화까지의 시간, 최대열방출률, 질량감소율 총방출열량 등의 지수에서 상압함침 처리보다는 도포 처리한 시험체가 더 높은 성능을 보였다.